An Experimental Study of the Effect of Wood Fuel Variations on Biomass Stove Performance - Sallolo Suluh; Frans Robert Bethony; Ermitha Ambun Rombe Dendo; Lery Alfriany Salo; Chendri Johan; Anselmus Aldi (Jurnal Riset Ilmu Teknik, 2026)
The performance of biomass stoves is influenced by fuel characteristics and operating conditions, including wood species and fuel mass. This study investigated the effects of wood species and initial fuel mass on the fuel consumption rate, thermal power, and thermal efficiency of a steam-injection biomass stove. Three wood fuels pine, fir, and coffee wood were tested at initial masses of 0.8, 1.0, and 1.2 kg, resulting in nine experimental conditions. The steam injector was supplied with 750 mL of water in each test. Stove performance was evaluated using the Water Boiling Test with 3 L of water at an initial temperature of 25°C. Fuel consumption, boiling duration, temperature, remaining fuel, charcoal, and water mass were recorded to calculate the fuel consumption rate, thermal power, and thermal efficiency. The results showed that increasing the initial fuel mass was accompanied by increases in fuel consumption rate and thermal power but decreases in thermal efficiency for all tested wood species. The highest fuel consumption rate and thermal power were observed with 1.2 kg of pine wood, reaching 0.0013 kg/s and 9.07647 kcal/s, respectively; however, its thermal efficiency was approximately 13%. In contrast, the highest thermal efficiency of 20% was obtained using 0.8 kg of fir wood. These findings demonstrate a trade-off between maximum heat output and efficient fuel-energy utilization. Under the tested conditions, pine wood at 1.2 kg was more suitable when high thermal output was prioritized, whereas fir wood at 0.8 kg provided the most favorable thermal efficiency. Further replicated experiments and statistical analyses are required to confirm the effects of wood species, fuel mass, and their interaction.